2021
DOI: 10.3390/ijerph18020566
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Violence in Adolescents and Youth Intimate Partner Relationships: Validation of the Spanish Version of the EAV

Abstract: The main purpose of the present study was to analyze the psychometric properties of the Attitudes Scale Towards Violence (Escala de Actitudes hacia la Violencia, EAV) in adolescents. The EAV is a questionnaire devoted to assess attitudes towards violence. Additionally, the relationship between EAV and violence manifestations and depressive symptoms was analyzed. The final sample comprised a total of 1248 students in a cross-sectional survey. The EAV, the Modified Conflict Tactics Scale (M-CTS), and the Reynold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Several authors defend the idea that IVAW and its acceptability can lead to more explicit and severe forms of IPV [ 62 , 63 , 64 , 65 ]. In fact, the WHO urges us to highlight gender attitudes and stereotypes that subjugate women and perpetuate male privilege, justifying violence against them [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors defend the idea that IVAW and its acceptability can lead to more explicit and severe forms of IPV [ 62 , 63 , 64 , 65 ]. In fact, the WHO urges us to highlight gender attitudes and stereotypes that subjugate women and perpetuate male privilege, justifying violence against them [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Close to this topic, and unfortunately becoming more frequent nowadays, is intimate partner violence. The work of Ortuño-Sierra et al [16] revealed that attitudes towards violence were more prevalent among men and that these attitudes were correlated with depressive symptoms. In addition, they confirmed the adequacy of an instrument for measuring this relevant construct that may allow one to prevent gender violence among adolescents.…”
mentioning
confidence: 99%